Islamic concept of food and its effects on Human beings - Dr. Samina Sadia; Dr. Farhat Aziz (jihat-ul-islam, 2020)
Nature has created all living beings with various instincts e.g., to live, to produce, survival etc. Survival is the utmost urge or necessity of all living organisms and for their survival, they need food, shelter, peace and civilization generated with the creation of human beings. Man gradually adopted himself with the environment of world, as the civilization evolved, man’s living style, eating and drinking habits and spiritual traits became refined. Civilization made man cultured, refined and gentle being to accommodate himself with society. A big revolution was brought about in human eating habits as human being ate raw material i.e., meat, vegetables, lentil etc, but gradually, they learnt to cook food with species. Islam lays one obligation or limitation on food-i.e, they must be Halal Pure and fresh. It demands people to eat and drink these things which are obtained through Halal ways because whatever we eat or drink, directly affects our body, mind, heart and soul. It has emphasized the fact that Haram forbidden food- make man animal, all parts of human beings i.e., Physical, intellectual, psycho moral, and spiritual are badly affected by Haram. Islam has provided a complete code of life to all individuals and masses for their living style, specially food, it’s law and etiquettes which motivate them to implement the religious laws and commandments in their practical lives.